Energy Barrier: Focus on the Essential: Extracting the Decisive Energy Barrier of a Complex Process (Adv. Mater. Interfaces 20/2019). Issue 20 (23rd October 2019) - Aeschlimann, Simon; Neff, Julia; Bechstein, Ralf; Paris, Chiara; Floris, Andrea; Kantorovich, Lev; Kühnle, Angelika
Abstract : How to extract the energy barrier of an individual step in a complex structural transition? In article number 1900795 by Simon Aeschlimann, Angelika Kühnle, and co‐workers, a strategy is presented to disentangle the involved steps by addressing all factors that impact the transition kinetics. The strategy is illustrated by determining the energy barrier for the dissociation of molecular dimers on a surface.